STATE INSTITUTIONS PROVIDING SERVICES FOR THE TOURISM PRODUCT IN KARAKALPAKSTAN AND THE HISTORY OF THE TOURISM COMMITTEE OF KARAKALPAKSTAN - Otenov, Nariman Turdymuratovich (SCIENCE and SOCIETY, 2026)
The article examines the activities of state institutions providing tourism services in the Republic of Karakalpakstan, as well as the history of the formation and development of the Karakalpakstan Tourism Committee. The tourism potential of the region and modern prospects for the development of the industry were also discussed.